Mindfulness-based Stress Reduction in Pregnancy: an App-Based Programme to Improve the Health of Mothers and Children (MINDFUL/PMI Study) - Lenz, Bernd; Eichler, Anna; Schwenke, Eva; Buchholz, Verena N.; Hartwig, Charlotte; Moll, Gunther; Reich, Karin; Mühle, Christiane; Volz, Bernhard; Titzmann, Adriana; Beckmann, Matthias; Heinrich, Hartmut; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Unfavourable intrauterine environmental factors increase the risk of delivery complications as well as postpartum developmental and behavioural problems in children and adolescents with ongoing effects into older age. Biomarker studies show that maternal stress and the use of alcohol and tobacco during pregnancy are associated with a higher intrauterine testosterone exposure of the child. The antenatal testosterone load, in turn, is a risk factor for lasting adverse health effects which extend into adulthood. A 15-week, mindfulness-oriented, app-based programme for the reduction of stress as well as for the reduction of alcohol and tobacco use in pregnant women is established. In the monocentre, prospective, controlled, and investigator-blinded MINDFUL/PMI (Maternal Health and Infant Development in the Follow-up after Pregnancy and a Mindfulness Intervention) study, pregnant women carry out the programme. Its effect on antenatal testosterone exposure of the child is examined by assessing the index/ring finger length ratio and other biomarkers in the 1-year-old children. In addition, the programme's effects on self-regulation, the developmental status and the mental health of the children at the age of one year will be investigated. Additional aspects of the course of the pregnancy and delivery represent exploratory study objectives. This longitudinal study project is intended to improve the understanding of the impact of intrauterine environmental factors on early childhood development and health. Maternal stress as well as alcohol and tobacco use during pregnancy are modifiable factors and represent potential preventive targets.
EVALuna2:36366

Physical activity and energy expenditure during depressive episodes of major depression - Wielopolski, Jan; Reich, Karin; Clepce, Marion; Fischer, Marie; Sperling, Wolfgang; Kornhuber, Johannes; Thürauf, Norbert (Journal of Affective Disorders, 2015)
Recent data suggest a substantial association between physical activity and depressive symptoms, but there is a lack of research evaluating the physical activity levels in patients suffering from unipolar depression across different stages of disease in an objective way. The aim of the present pilot study was to objectively examine physical activity levels of this patient group compared to healthy controls.Physical activity performance of 19 patients with major depressive episode and 19 healthy controls was assessed at three different time points using a multisensory armband device (SenseWear® Pro3 Armband) and was reported as total energy expenditure (TEE), active energy expenditure (EE), metabolic equivalents (METs), physical activity (PA) and time of lying down (LD), in each case over 24h.Over all measurements, depressive patients presented a significantly lower mean TEE and EE over 24h. Moreover, the patient group showed significantly shorter duration of PA and lower average MET over 24h. When depressive symptoms abated, physical activity parameters significantly increased in the patient group. Correlation analyses demonstrated a significant relation between depressive status/anhedonia and parameters of physical activity, especially in healthy subjects.Results represented valid data for inpatients only.Acute unipolar depression was associated with a significantly lower level of physical activity and showed a significant increase in parallel to clinical improvement. Electronic monitoring of physical activity may be an additional tool for evaluating and controlling therapeutic effects.
EVALuna2:23724

The hedonics of olfactory induced memories - a new model for the analyses of emotional blunting - Thürauf, Norbert; Sollmann, Manuel; Fuchs, Michael; Jäger, Jakob; Mettang, Melissa; Reich, Karin; Kornhuber, Johannes; Sperling, Wolgang; Freiherr, Jessica (CHEMICAL SENSES, 2020)
CRIS-Team WoS Importer:2020-06-23

The psychophysical assessment of odor valence: does an anchor stimulus influence the hedonic evaluation of odors? - Clepce, Marion; Neumann, Konrad; Martus, Peter; Nitsch, Marie; Wielopolski, Jan; Koch, Anna Maria; Kornhuber, Johannes; Reich, Karin; Thürauf, Norbert (Chemical Senses, 2014)
Olfactory stimuli are experienced primarily in terms of their hedonic tone and the assessment of olfactory hedonic estimates is a prevalent task in scientific and industrial contexts. However, measuring conditions are poorly standardized. Our study aims to fill this gap, focusing on the influence of anchor stimuli on olfactory hedonic evaluations, frequency of anchor presentation, and temporal stability of results. In n = 31 subjects, hedonic estimates for the 16 odors of the Sniffin' Sticks identification task were assessed on a visual analog rating scale under 4 measuring conditions (nonanchor, pleasant anchor, neutral anchor, unpleasant anchor). To test for stability over time, n = 10 subjects were reassessed 2, 4, and 6 months after original testing. To analyze for possible effects of single versus repeated anchor presentation, n = 15 subjects were retested 2 months after the original session in a multiple anchor presentation format. Statistical analysis revealed significant differences between the 4 anchor conditions, thus highlighting the necessity of specifying assessment methods in scientific research. No significant differences between timepoints were observed, indicating a high temporal stability of olfactory hedonic evaluations, especially from timepoint T2 onward. No overall significant effects of single versus multiple anchor presentation were detected. Findings might help to further standardize testing procedures.
EVALuna2:23574